The Position of Women in Perspective of Islamic History: Dismissed the Issue of Inequality in Islam: Kedudukan Perempuan Dalam Perspektif Sejarah Islam: Menepis Isu Ketidaksetaraan Gender Dalam Islam - Arfah (Indonesian Journal of Islamic History and Culture, 2024)
Islam is a fair religion in its view of the status of women, unlike the pre-Islamic culture that degraded them. Islam has elevated the status of women from an era that demeaned them to one that grants balanced rights between men and women. However, there are still some who tarnish Islam with gender issues. In reality, Islam was the first to express gender equality found in the Quran, with many verses implying a fair gender equality concept for both men and women. Throughout history, we find many Muslim women playing significant roles in advancing Islamic civilization worldwide. This demonstrates that the presence of Islam honours and accepts women in various aspects of life, enabling them to contribute to the advancement of Islamic civilization. This has led to the emergence of many Muslim women figures known today who have made history in the Islamic world.